Conceptions of Shari`a and Support for Militancy and Democratic Values: Evidence From Pakistan*. Issue 3 (25th January 2017) - Fair, C. Christine; Littman, Rebecca; Nugent, Elizabeth R.
Abstract : Numerous empirical studies of the relationship between popular support for Islamism and support for democracy and violence have yielded inconclusive results. We suspect that this is largely because scholars have not operationalized support for Shari`a in ways that capture the concept's multi-dimensionality. In this paper, we employ data derived from a carefully designed survey instrument that casts unique insights into how Pakistanis imagine a Shari`a -based government. We find that formalizing an Islamic government as one that implements Shari`a by providing services and security for its citizens is positively associated with support for democratic values, whereas conceptualizing it as one that implements Shari`a by imposing hudud punishments and restricting women's public roles is positively associated with support for militancy. These results suggest that it is important to understand how individuals within a particular context construe a Shari`a -based government, and future empirical work should take this.